Testosterone and testosterone plus 17 beta-estradiol prostatic hyperplasia induced in castrated rats - Gonzáles, Carlos (1996)
Begin prostatic hyperplasia etiology is still unknow. It is believed that estradiol (E2) is involved. The objetive of this study was to determine the E2 action in the prostatic proloferation induced in castrated rats. The experimental was randomized in 3 independent groups during 4 weeks; the first one, control without treatment; the second one, castrated and testosterone enantate (TE) treated; and the third one, castrated and TE plus 17 beta-estradiol hemisuccinate treated. Weight prostatic difference was studied with the U test, histology with light-microscopy. Weight prostatic difference between the second and third groups as in the significance limit (P=0.05). Histologically increase in secretion and hyperplasia was noted in the third group. We concluded that E2 synergizes testosterone proliferating action upon the prostate and this could account for benign prostatic hyperplasis genesis.